Processing of turmeric (Curcuma longa) by different curing methods and its effect on quality - JAYASHREE, E; ZACHARIAH, T JOHN (The Indian Journal of Agricultural Sciences, 2016)
The results of the study on curing Prathiba variety turmeric by eight different curing methods indicated that slicing significantly reduced the drying time to 9 days. Turmeric cured by cooking in boiling water for 40, 60, 90 min, took 11 days for complete drying. While turmeric rhizomes cured by steam cooking for 30, 45 and 60 min took 24, 23 and 12 days for drying. Increase in curing time of turmeric rhizomes resulted in significant reduction in curcumin, starch, essential oil and oleoresin content. In case of water boiling method, maximum retention of curcumin (5.91%) and essential oil (3.6%) was obtained for rhizomes cured for 40 min. While in the case of steam boiling method, the maximum retention of the quality parameters was obtained at 30 min steaming when the curcumin content (6%), essential oil content (3.33%), oleoresin content (13.96%) and starch content was highest (63.33%). But, the drying time was longest (24 days) at this curing level. However, the steam cooking had several advantages over traditional cooking by water boiling in terms of fuel consumption and the quantity of rhizomes that could be cured per batch and also reduction of labour.